Analisis Kemampuan Konsep Perkalian pada Pembelajaran Matematika Siswa Kelas II Ditinjau dari Teori Behavioristik - Della Ayu Puspita; Lovika Ardana Riswari; Diana Ermawati (JANACITTA, 2025)
Abstract Conceptual abilities can be expressed specifically in the context of changing behavior, re-expressing a concept, using a concept and being able to develop a concept. Changes in behavior experienced by students due to stimulus and responsse are called behaviorist theory, stimulus is whatever the teacher gives to the student while responsse is the student's responsse to the stimulus the teacher provides. The aim of this research is to analyze the ability of multiplication concepts in class II students' mathematics learning in terms of behavioristic theory. The population in this study were 9 students in grade II at SDN 3 Piji and the sample in this study was 3 students. This research uses a qualitative descriptive research type. The number of subjects that the researcher used was 3 using a purposive technique based on the criteria used by the researcher in the form of high students, medium students, and low students. Data collection techniques use observation, interviews and documentation. Data analysis techniques according to Miles and Huberman which include data reduction, data presentation, and drawing conclusions. The results of research at SDN 3 Piji show that the multiplication concept ability seen from behavioristic theory of students in the high student category shows changes in behavior such as being fluent in memorizing multiplications, memorizing multiplications and working on questions without help from the teacher. Students in the medium category showed changes in behavior such as not being fluent in memorizing multiplications and when memorizing multiplications students still counted using their fingers. Students in the low category show changes in behavior such as not being fluent in memorizing multiplications, not calculating multiplications but immediately answering with naughty answers and still needing help from the teacher. Abstrak Kemampuan konsep dapat dinyatakan secara khusus dalam konteks perubahan tingkah laku, mengungkapkan kembali sebuah konsep, menggunakan konsep dan dapat mengembangkan konsep. Perubahan tingkah laku yang dialami oleh siswa karena adanya stimulus dan respons disebut teori behavioristik, stimulus adalah apa saja yang diberikan oleh guru kepada siswa sedangkan respons adalah tanggapan siswa atas stimulus yang guru berikan. Tujuan penelitian ini adalah untuk menganalisis kemampuan konsep perkalian pada pembelajaran matematika siswa kelas II ditinjau dari teori behavioristik. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Populasi pada penelitian ini adalah siswa kelas II di SDN 3 Piji yang berjumlah 9 siswa dan sampel pada penelitian ini berjumlah 3 siswa. Subjek yang peneliti gunakan berjumlah 3 menggunakan teknik purposive berdasarkan kriteria yang digunakan peneliti berupa siswa tinggi, siswa sedang, siswa rendah. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Teknik analisis data menurut Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian di SDN 3 Piji menunjukkan bahwa kemampuan konsep perkalian dilihat dari teori behavioristik siswa dengan kategori siswa tinggi menunjukkah perubahan tingkah laku seperti lancar dalam menghafal perkalian, menghafal perkalian dan mengerjakan soal tanpa bantuan dari guru. Siswa dengan kategori sedang menunjukkan perubahan tingkah laku seperti belum lancar dalam menghafal perkalian dan saat menghafal perkalian siswa masih menghitung menggunakan jari. Siswa dengan kategori rendah menunjukkan perubahan tingkah laku seperti tidak lancar dalam menghafal perkalian, tidak menghitung perkalian tetapi langsung menjawab dengan jawaban yang sembarangan dan masih memerlukan bantuan dari guru.